Effect of a serious game JeStiMulE in emotion recognition of Moroccan autistic children - MAMMAD, Khaoula (Universitas Ahmad Dahlan, 2018)
Human beings can express their emotions in different ways such as facial expressions, bodily expressions, prosody, or language. However, ASDs are life-long neurodevelopmental disorders characterized by varying levels of social and communicative defcit. The influence of a